ACSM's Foundations of Strength and Conditioning - Ratamess Nicholas (Wolter Kluwer Lippincott Wlliams & Wilkins, 2012)
This text offers a comprehensive introduction to the basics of strength training and conditioning based on the latest research findings. Preface, User's Guide, Reviewers, Acknowledgements, Foundations, Introduction to Strength Training and Conditioning, Biomechanics of Force Production, Physiological Responses and Adaptations, Neural Adaptations to Training, Muscular Adaptations to Training, Connective Tissue Adaptations to Training, Endocrine Systems Responses and Adaptations, Metabolic Responses and Adaptations of the Cardiorespiratory System, Principles of Strength Training and Conditioning, Strength Training and Conditioning Program Design, Warm-Up and Flexibility, Resistance Training Program Design, Resistance Training Equipment and Safety, Resistance Training Exercises, Plyometric Training, Sprint and Agility Training, Aerobic Training, Training Periodization and Tapering, Assessment, Assessment and Evaluation, Glossary, Index.